2022
DOI: 10.1227/neu.0000000000002237
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Growth Rate in Spinal Giant Cell Tumors of Bone and Association With the Immune Microenvironment and Denosumab Treatment Responsiveness: A Multicenter Study

Abstract: BACKGROUND:Currently, little is known about the prognostic value of tumor growth rate (TGR) in spinal giant cell tumors of bone (GCTB).OBJECTIVE:To investigate the correlation of TGR with clinicopathological features, immune microenvironment, prognosis, and response to denosumab treatment of spinal GCTB.METHODS:A total of 128 patients with spinal GCTB treated at 5 centers from 2011 to 2021 were included. TGR was assessed by 2 independent neuroradiologists using at least 2 preoperative thin-section magnetic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In order to further investigate, the immunological characteristics of chordomas and their association with clinical parameters, we used the X-tile software to determine the threshold for survival analysis, we divided the IS and TLS into high and low groups according to the cut-off point. 8 We found that higher IS and TLS were associated with poorer prognosis (p=0.0012 and p<0.001, respectively, figure 1A,B).…”
Section: Immune Featuresmentioning
confidence: 63%
“…In order to further investigate, the immunological characteristics of chordomas and their association with clinical parameters, we used the X-tile software to determine the threshold for survival analysis, we divided the IS and TLS into high and low groups according to the cut-off point. 8 We found that higher IS and TLS were associated with poorer prognosis (p=0.0012 and p<0.001, respectively, figure 1A,B).…”
Section: Immune Featuresmentioning
confidence: 63%
“…Immunohistochemical staining was conducted as previously delineated [ 7 , 9 ]. In brief, 4 μm paraffin-embedded sections of 427 GCTB specimens from four institutes were deparaffinized in xylene, rehydrated using a series of graded ethanol solutions, and rinsed in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the widespread utilization of the Campanacci staging system for guiding clinical management and stratifying prognostic risk, robust predictive models remain wanting in comparison to their counterpart [ 5 ]. Although certain molecular markers have been identified as related to the survival and prognosis of GCTB, their study is restricted to the molecular level, thereby risking the dissemination of imprecise prognostic information [ 6 , 7 ]. Furthermore, the stromal cells and tumor cells within the microenvironment are intricately linked [ 8 , 9 ], and the tumor stroma is recognized to play a crucial role in tumor formation, progression, invasion, and metastasis [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…LRFS was defined as the duration between tumor resection and the first recurrence, while OS referred to the time from surgical resection to the patient’s death from any cause [ 12 ]. The type of surgical resection was determined based on a previously reported method [ 13 ], distinguishing between wide resection (such as gross total or en bloc resection with negative margins) and non-wide resection (including intralesional or marginal resection).…”
Section: Methodsmentioning
confidence: 99%